THE INFLUENCE OF AGE AND PSYCHOLOGICAL DEVELOPMENT ON THE LEARNING OF THE FRENCH LANGUAGE (Eureka Journal of Language, Culture & Social Change, 2026)
This article analyzes the role of age and psychological development in learning French. It has been scientifically proven that language learning effectiveness is closely linked to the learner's age characteristics, level of cognitive and emotional development, as well as motivation and psychological environment. The article also examines effective methods and psychopedagogical approaches to teaching French at different age levels. It helps identify the role of age and psychological development factors in learning French and effective teaching methods based on them.
Keywords: Age factor, psychological development, motivation, teaching methodology, psychopedagogy, cognitive development, individual approach, educational psychology, communicative approach, emotional state, learning strategies, psychological environment, speech skills, language competence.